Upaya Penghematan Air Gedung Perkantoran Industri Pupuk - Arini Sayyidah Achmad; Firra Rosariawari (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Clean water is a basic human need. Company activities, especially in office areas, require the availability of water that is large enough to move during the work period. One of them is an office area in one of the Fertilizer Industries. The purpose of this research is to identify efforts to save clean water in the office area of one of the fertilizer industries to increase awareness of environmental conditions. This study was conducted by calculating the efficiency of water saving after water-saving efforts were made. Efforts made include monitoring water meters, using water-saving taps, using flushes in toilets, and using sprinklers in plants sprinklers. The use of water-saving faucets uses push taps where the faucet will close automatically when turned on after a while. And for the flush system used, namely dual flush toilets. The The dual flush system has two types of watering.